A New Code for Automatic Detection and Analysis of the Lineament Patterns for Geophysical and Geological Purposes (Adalgeo) - Sanchez-Munoz, G; Arellano-Baeza, A; Soto-Pinto, C (2013)
Sin Editorial Disponible